Isolated Pancreatic Transplantation in a Brazilian Centre - Nicoluzzi, João Eduardo (2008)
Purpose. Simultaneous pancreas-kidney transplantation (SPK) is an accepted treatment for patients with type 1 diabetes mellitus and end- stage renal disease. Modern immunosuppression and biopsy techniques have improved the success of pancreas alone (PA) transplantations to the point where the outcome is now equivalent to that of SPK. Methods. From 120 pancreas transplants at Angelina Caron Hospital since 2001, 12 were PA transplants. Results. Patient and graft survival rates at 1 year were respectively 83 % and 75 %. Two patients died due to sepsis in the first and second month after surgery, both with functioning grafts. One graft was lost due to venous thrombosis during the fist transplant week. Patient survival rate was 100 % at hospital discharge. Conclusion. The present report describes our data with PA transplantation with fine results for a limited experience in such transplantation modality.